Comparisons of Serum Progesterone and Progestagen Concentrations in Normal and Abnormal Bottlenose Dolphin (Tursiops truncatus) Pregnancies - Robeck, Todd R.; Steinman, Karen J.; Parry, Celeste B.; Gomez, Forrest M.; Jensen, Eric D. (Frontiers in Marine Science, 2021)
Although previous studies have described progesterone profiles during pregnancy in the bottlenose dolphin (Tursiops truncatus), most of these focused on normal pregnancy (NORM) or compared NORM to only one or two abnormal pregnancy types, such as abortion (AB) or perinatal loss (PNL). Hormonal pregnancy biomarker analysis from reproductive events with different outcomes may reveal differences in concentrations so that we are able to identify high risk pregnancies. The aim of this study was to describe longitudinal profiles of circulating progesterone and progestagens during reproductive events in the female bottlenose dolphin, including NORM, failure to thrive, PNL, AB, early loss (EL) and false pregnancy (FP). Progesterone differed from NORM during EL at EARLY (month post conception [MPC] 1-4), AB at MID (MPC 5-8) and FP at LATE (MPC 9-12) stages. Progestagens differed from NORM during AB and FP at MID and LATE stages and during MPC 12 in PNL and MPC 4 in EL. Progestagens may be better at predicting poor reproductive outcome in the bottlenose dolphin and a suite of hormone tests, including progesterone and progestagens, should be incorporated into existing clinical diagnostic and management practices in this species. Furthermore, analysis of multiple hormonal pregnancy biomarkers from a single sample may enable pregnancy diagnosis sample for wild animals.